Epidermal growth factor receptor: Role in human cancer - Prashanth Rajaram; Poornima Chandra; Smriti Ticku; B K Pallavi; K B Rudresh; Poorva Mansabdar (Wolters Kluwer Medknow Publications, 2017)
Cells are constantly exposed to various external stimuli which regulate the growth and survival of the cells. The signal transduction from the external environment to the interior of the cell is carried out by cell surface or transmembrane receptors. Epidermal growth factor receptor (EGFR) is a type I receptor tyrosine kinase and along with its ligands, EGFR is involved in the regulation of multiple cellular pathways. EGFR and its signaling pathway have been studied extensively for the biological and pathophysiological role in health and disease. There is enough evidence to suggest that EGFR is involved in the pathogenesis and progression of various cancers. This review discusses the structural anatomy and physiology of EGFR and its ligands, the role of EGFR in cancer and EGFR-targeted therapy.